Tort Penalty on the Judge in the Light of Legal Maxims and Pakistani’s Laws - Hafiz Muhammad Ishaq; Humayun Abbas (Journal of Islamic and Religious Studies, 2018)
A judge should be honest, transparent, free and fair. He should always respect law. The question arises that if a judge who disrespects law and makes unbalanced decisions: as a result of which people get affected then will he or she be penalized? The Ḥanafi Scholars opine that if a judge passes a wrong decision intentionally, he should be penalized from his own property. Because in Islamic jurisprudence, judiciary owns a supremacy over the masses and everyone irrespective of the position is equal and has to obey law. Whether he is a judge or a commoner, he has to follow the rules and regulations as prescribed by law. In practice, Pakistani judges are not held responsible for making a wrong verdict. Our judges make judgments on the basis of already manipulated evidence. A judge bars himself from the responsibility of collecting evidence. Similarly, if a judge has developed personal grudges with the criminal then the criminal reserves right of appealing the higher court where the decision is reviewed and rectified. In such situation, there is a compulsion between the legal maxim "وَالْأَصْلُ عَدَمُ الضَّمَان" and the Pakistani laws. However, Ḥanafi jurisprudence and Pakistani Laws are not in accordance with each other. This study concentrates upon the nature of punishment and tort to be applied on judges in case of making a decision based on falsehood. It is suggested that Pakistan’s Judiciary should be reread as that the already in-practice system does not comply with the standards of Islamic teachings.